Book Review: Rajeev Malhotra, Indian Public Policy Report 2014. Issue 3 (December 2016) - Chakravarty, Debabani; Dutta, Pankaj
Rajeev Malhotra, Indian Public Policy Report 2014 . New Delhi: Jindal School of Government and Public Policy and Oxford University Press, 2014, ₹782, 264 pp.